Mulheres em trânsitos poligâmicos: uma leitura de O alegre canto da perdiz, de Paulina Chiziane - Carvalho, Larissa Peres Vitti de (Universidade Federal de São Carlos, 2020)
This research aims to analyze the novel O alegre canto da perdiz (2008), by Mozambican writer Paulina Chiziane, through a reading on the thematic axis of polygamy, seeking to observe its preponderance within the fictional constructions of her literary project. Taking as a starting point of discussion some theoretical and conceptual assumptions of post-coloniality and their connections with the articulation of the theme under study, the intention here is to investigate and demonstrate how the novel invests in reflecting on the role of women within the Mozambican society.
Women in polygamic transit: a reading of O alegre canto da perdiz, by Paulina Chiziane
Keywords: Poligamia; Autoria feminina; Ficção moçambicana contemporânea; Paulina Chiziane; Poligamy; Female authorship; Contemporary Mozambican fiction; LINGUISTICA, LETRAS E ARTES::LETRAS::OUTRAS LITERATURAS VERNACULAS